The usefulness of standardized uptake value in differentiation between benign and malignant thyroid lesions detected incidentally in 18F-FDG PET/CT examination. - Adam Stangierski (Public Library of Science (PLoS), 2014)
Introduction In the last decade, (18)F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET and PET/CT) has become one of the major diagnostic tools used in oncology. A significant number of patients who undergo this procedure, due to non-thyroidal reasons, present incidental uptake of (18F-FDG) in the thyroid. The aim of the study was to compare the SUVmax (standardized uptake value) of thyroid focal lesions, which were incidentally found on PET/CT, in relation to the results of thyroid fine-needle aspiration biopsy (FNAB) and/or histopathological evaluation. Materials and methods Patients referred for PET/CT examination, due to non-thyroidal illness, presented focal 18F-FDG uptake in the thyroid and were advised to undergo ultrasonography (US), hormonal evaluation, FNAB and/or total thyroidectomy at our institution. Results 6614 PET/CT examinations performed in 5520 patients were analyzed. Of the 122 patients with focal thyroid 18F-FDG activity, 82 patients (67.2%) underwent further thyroid evaluation using FNAB. Benign lesions were diagnosed in 46 patients, malignant - in 19 patients (confirmed by post-surgical histopathology), while 17 patients had inconclusive results of cytological assessment. Mean SUVmax of benign lesions was 3.2±2.8 (median = 2.4), while the mean SUVmax value for malignant lesions was 7.1±8.2 (median = 3.5). The risk of malignancy was 16.7% for lesions with a SUVmax under 3, 43.8% for lesions with a SUVmax between 3 and 6, and 54.6% for lesions with a SUVmax over 6. In the group of malignant lesions, a positive correlation between the lesion's diameter and SUVmax was observed (p = 0.03, r = 0.57). Conclusions Subjects with incidental focal uptake of 18F-FDG in thyroid are at a high risk of thyroid malignancy. A high value of SUVmax further increases the risk of malignancy, indicating the necessity for further cytological or histological evaluation. However, as SUVmax correlated with the diameter of malignant lesions, small lesions with focal uptake of 18F-FDG should be interpreted cautiously.